Reflect Action Methods - and ActionAid (2009)
Reflect is an innovative approach to adult learning and social change, which fuses the theories of Brazilian educator Paulo Freire with participatory methodologies. It was developed in the 1990s through pilot projects in Bangladesh, Uganda and El Salvador and is now used by over 500 organisations in over 70 countries worldwide. Organisations working with Reflect won UNESCO literacy prizes in 2003, 2005, 2007, 2008 and 2010. This site is aimed at Reflect practitioners and others who want to know more about the approach. We want it to be truly interactive and the more stories, graphics and photos are submitted, the better the site will be. Please add your comments to tell us about the work you are doing with Reflect and join the discussion forum to share your ideas and experiences of working with the approach.